2017
DOI: 10.2147/ijn.s129324
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate carried in lipid core nanoparticles reduces myocardial infarction size and improves cardiac function in rats

Abstract: Purpose Acute myocardial infarction (MI) is accompanied by myocardial inflammation, fibrosis, and ventricular remodeling that, when excessive or not properly regulated, may lead to heart failure. Previously, lipid core nanoparticles (LDE) used as carriers of the anti-inflammatory drug methotrexate (MTX) produced an 80-fold increase in the cell uptake of MTX. LDE-MTX treatment reduced vessel inflammation and atheromatous lesions induced in rabbits by cholesterol feeding. The aim of the study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 48 publications
4
21
0
3
Order By: Relevance
“…SR‐BI is expressed in several cell types relevant to inflammatory and proliferative processes, including monocytes, macrophages, dendritic cells, platelets, and neoplastic cells (Hoekstra, ; Wang et al, ; Yuan et al, ). The finding of increased expression of SR‐BI in the noninfarcted myocardial area was therefore expected, since all these cells are present in greater number in the post infarcted myocardium, as we previously documented (Maranhão et al, ).…”
Section: Discussionsupporting
confidence: 77%
“…SR‐BI is expressed in several cell types relevant to inflammatory and proliferative processes, including monocytes, macrophages, dendritic cells, platelets, and neoplastic cells (Hoekstra, ; Wang et al, ; Yuan et al, ). The finding of increased expression of SR‐BI in the noninfarcted myocardial area was therefore expected, since all these cells are present in greater number in the post infarcted myocardium, as we previously documented (Maranhão et al, ).…”
Section: Discussionsupporting
confidence: 77%
“…In a rat model of reperfused MI, cyclophosphamide administration attenuated leukocyte infiltration and reduced ventricular dysfunction (Zhu et al, ). Methotrexate treatment was also found to exert protective effects on the ischaemic and reperfused myocardium in both large animal (Asanuma et al, ) and rodent models (Maranhao et al, ). However, in a small clinical trial, methotrexate administration to patients with STEMI did not affect acute infarct size and worsened systolic dysfunction 3 months after the acute event (Moreira et al, ).…”
Section: Broad Anti‐inflammatory Interventionsmentioning
confidence: 99%
“…Effect of paeoniflorin on cardiac remodeling in chronic heart failure rats through the transforming growth factor β1/Smad signaling pathway role in the development of cardiac remodeling (3)(4)(5). Previous studies have found that methotrexate, rapamycin and triptolide can regulate inflammatory responses, alleviate cardiac fibrosis and improve cardiac function in rats (6)(7)(8). Therefore, more and more scholars all over the world began to explore the application value of anti-inflammatory and immunomodulation strategy in CHF.…”
Section: Original Articlementioning
confidence: 99%